Policy Deficit in Distance Education: A Transactional Distance - Gokool-Ramdoo, Sushita (International Review of Research in Open and Distributed Learning, 2009)
This paper innovatively extends the application of transactional distance theory (TDT) to evidence-based policy development in Mauritius. In-depth interview data on student persistence from a range of stakeholders is used to understand the implications of distance education (DE) policy deficit. Policy deficit has surfaced as another dimension of transactional distance and student persistence as an appropriate measuring instrument. Transactional distance is salient in the non-alignment of national and institutional DE planning. Associated results are myopic institutional vision, stagnating national plans, poor resource deployment, and ill-understood opportunities for personal development. This research validates TDT as an instrument for policy development and concludes that supporting advocacy plans will help to achieve sustainable distance education in the region. Lessons from the field in Mauritius can be usefully adapted to the sub-Saharan African context (SSA). These preliminary indications require further research and discussion.